Synthesis and characterization of iron doped ZnO hollow spheres Via hydrothermal method - Lachom, Vichuda; Laokul, Paveena (Science Essence Journal, 2018)
บทคัดย่อ ZnO ทรงกลมกลวงพื้นผิวพรุนเจือด้วย Fe ที่มีปริมาณการเจือเป็น 0% , 0.5% และ 1.0% ถูกเตรียมด้วยวิธีไฮโดรเทอร์มอล สารตั้งต้นถูกนำไปแคลไซน์ในอากาศที่อุณหภูมิ 400, 500 และ 600oC เป็นเวลานาน 2 ชั่วโมง สารตัวอย่างที่เตรียมได้ถูกนำมาศึกษาด้วยเทคนิค TG, XRD, TEM, SEM, EDX และ UV-visible spectroscopy จากผลการศึกษาด้วยเทคนิค XRD พบว่า สารตัวอย่างมีโครงสร้างผลึกแบบเฮกซะโกนอลเวิร์ธไซต์โดยไม่พบเฟสเจือปน จากรูปถ่าย SEM พบว่า ลักษณะทางสัณฐานของสารตัวอย่างมีลักษณะทรงกลมกลวงพื้นผิวพรุนโดยมีเส้นผ่านศูนย์กลางประมาณ 3 ไมโครเมตร โดยขนาดเส้นผ่านศูนย์กลางของทรงกลมมีค่าลดลงเมื่อปริมาณการเจือ Fe มีค่าเพิ่มขึ้น จากการตรวจสอบด้วยเทคนิค TEM พบว่าสารตัวอย่างทั้งหมดมีขนาดอนุภาคเดี่ยวเฉลี่ยในระดับนาโนเมตร เมื่อพิจารณาลักษณะทางสัณฐานพบว่าอนุภาคเดี่ยวมีรูปทรงเรขาคณิตหลายเหลี่ยม ขนาดช่องว่างแถบพลังงานของสารตัวอย่างที่ได้จากการวิเคราะห์สเปคตรัมการดูดกลืนด้วยเทคนิค UV-vis พบว่ามีค่าอยู่ในช่วง 3.01-3.11 eV อนุภาคทรงกลมกลวงพื้นผิวพรุน ZnO เจือด้วย Fe ที่เตรียมได้มีศักยภาพที่จะใช้ในกระบวนการเร่งปฏิกิริยาด้วยแสงเพื่อการบำบัดน้ำเสีย คำสำคัญ: ZnO เจือด้วย Fe ผลึกระดับนาโนเมตร โครงสร้างทรงกลมกลวง วิธีไฮโดรเทอร์มอล ABSTRACT Porous Fe-doped ZnO hollow spheres with Fe contents of 0%, 0.50% and 1.0% were prepared by hydrothermal method. The precursor powders were calcined in air at the temperature of 400 500 and 600oC for 2 h. The obtained samples were analyzed by TG, XRD, TEM, SEM, EDX and UV-visible spectroscopy. The results from XRD showed that all the samples possessed hexagonal wurtzite structure with no impurity phase. SEM images revealed that the obtained samples were hollow structure with diameter around 3 µm. The diameter of hollow sphere tends to decreased with increasing Fe content. The primary particle morphology and sizes of all samples were investigated by TEM technique and the result showed that ZnO and Fe-doped ZnO particles had polygon geometry in nanometer scale. The energy band gap () of the sample was evaluated using UV–vis absorption spectra and it found to be in the range of 3.01–3.11 eV. The obtained porous Fe-doped ZnO hollow spheres have the potential to be used in the photocatalysis process for wastewater treatment. Keywords: Fe doped ZnO, Nanocrystalline, Hollow sphere structure, Hydrothermal method